Channelrhodopsin-1 phosphorylation changes with phototactic behavior and responds to physiological stimuli in Chlamydomonas. - Böhm, Michaela; Boness, David; Fantisch, Elisabeth; Erhard, Hanna; Frauenholz, Julia; Kowalzyk, Zarah; Marcinkowski, Nadin; Kateriya, Suneel; Hegemann, Peter; Kreimer, Georg (The Plant Cell, 2019)
The unicellular alga Chlamydomonas reinhardtii exhibits oriented movement responses (phototaxis) to light over more than three log units of intensity. Phototaxis thus depends on the cell's ability to adjust the sensitivity of the involved photoreceptors to the ambient light conditions. In C. reinhardtii these are the channelrhodopsins ChR1 and ChR2, which are plasma membrane located light-gated cation channels. Although ChRs are widely used in optogenetic studies, knowledge about ChR signaling in alga is still limited. We characterized the in vivo phosphorylation of ChR1. Its reversible phosphorylation occurred within seconds as a graded response to changes in the light intensity and ionic composition of the medium and depended on an elevated cytosolic Ca2+ concentration. Changes in the phototactic sign were accompanied by alterations in the ChR1 phosphorylation status. Furthermore, compared with the wild-type, a permanently negative phototactic mutant required higher light intensities to evoke ChR1 phosphorylation. C-terminal ChR1 truncation disturbed the reversible phosphorylation, whereas it was normal in ChR2-knockout and eyespot-assembly mutants. Newly identified phosphosites in regions important for ChR1 function point to their potential regulatory role(s). We propose that multiple ChR1 phosphorylation, regulated via a Ca2+-based feedback loop, is one important component in the adaptation of phototactic sensitivity in Chlamydomonas.

Proteomic Analysis of a Fraction with Intact Eyespots of Chlamydomonas reinhardtii and Assignment of Protein Methylation - Eitzinger, Nicole; Wagner, Volker; Weisheit, Wolfram; Geimer, Stefan; Boness, David; Kreimer, Georg; Mittag, Maria (Frontiers in Plant Science, 2015)
Flagellate green algae possess a visual system, the eyespot. In Chlamydomonas reinhardtii it is situated at the edge of the chloroplast and consists of two carotenoid rich lipid globule layers subtended by thylakoid membranes (TM) that are attached to both chloroplast envelope membranes and a specialized area of the plasma membrane (PM). A former analysis of an eyespot fraction identified 203 proteins. To increase the understanding of eyespot related processes, knowledge of the protein composition of the membranes in its close vicinity is desirable. Here, we present a purification procedure that allows isolation of intact eyespots. This gain in intactness goes, however, hand in hand with an increase of contaminants from other organelles. Proteomic analysis identified 742 proteins. Novel candidates include proteins for eyespot development, retina-related proteins, ion pumps, and membrane-associated proteins, calcium sensing proteins as well as kinases, phosphatases and 14-3-3 proteins. Methylation of proteins at Arg or Lys is known as an important posttranslational modification involved in, e.g., signal transduction. Here, we identify several proteins from eyespot fractions that are methylated at Arg and/or Lys. Among them is the eyespot specific SOUL3 protein that influences the size and position of the eyespot and EYE2, a protein important for its development.
Keywords: ATP synthase; Chlamydomonas reinhardtii; EYE2; eyespot proteome; phototaxis; protein methylation; SOUL hems-binding protein 3